2018
DOI: 10.1158/0008-5472.can-17-1980
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Type I Interferon to Dendritic Cells Empowers Tumor Eradication and Immune Combination Treatments

Abstract: An ideal generic cancer immunotherapy should mobilize the immune system to destroy tumor cells without harming healthy cells and remain active in case of recurrence. Furthermore, it should preferably not rely on tumor-specific surface markers, as these are only available in a limited set of malignancies. Despite approval for treatment of various cancers, clinical application of cytokines is still impeded by their multiple toxic side effects. Type I IFN has a long history in the treatment of cancer, but its mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 57 publications
3
66
0
1
Order By: Relevance
“…Quite similar to wtTNF, mCD13‐AFR induced expression of both ICAM‐1 and E‐selectin and repression of VEGF‐R2 at 4 h after injection. Since tumor‐bearing mice tend to be sensitized toward TNF toxicity (Cauwels et al , 2018b), we next tested mCD13‐AFR in the B16Bl6 melanoma model. In stark contrast to wt TNF, daily treatment for 10 consecutive days with a therapeutic dose of mCD13‐AFR caused no significant weight loss or other apparent toxicity, confirming its safety (Fig E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quite similar to wtTNF, mCD13‐AFR induced expression of both ICAM‐1 and E‐selectin and repression of VEGF‐R2 at 4 h after injection. Since tumor‐bearing mice tend to be sensitized toward TNF toxicity (Cauwels et al , 2018b), we next tested mCD13‐AFR in the B16Bl6 melanoma model. In stark contrast to wt TNF, daily treatment for 10 consecutive days with a therapeutic dose of mCD13‐AFR caused no significant weight loss or other apparent toxicity, confirming its safety (Fig E).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore no surprise that TNF can synergize with immunotherapies such as IL‐2 (Schwager et al , ; Danielli et al , ,b; De Luca et al , ) or adoptive T‐cell transfer (Johansson et al , ). We have previously reported that low‐dose TNF therapy potentiated DC‐targeted AFN therapy (Cauwels et al , 2018b). Here, we show the remarkable synergy of vasculature‐targeted AFR therapy with mCD8‐AFN, targeting cytotoxic T cells (and the cDC1 subset of DCs), leading to profound B16Bl6 tumor elimination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another approach for DC subset-specific targeting employs vaccination with nanoparticles (encapsulating TAAs and TLR ligands) conjugated with the above-mentioned antibodies to avoid damaging systemic inflammation. This nanoparticle-based approach can potentially also be used to deliver cytokines, short or long peptides, total protein or RNA molecules to the target cells 24 .…”
Section: In Vivo DC Targetingmentioning
confidence: 99%